Pedologic indicators of phaseolus vulgaris crops in the colombian dry caribbean, in situ strategy - Velasquez Agudelo, Andres David; Tofiño Rivera, Adriana Patricia; Zapata Tamayo, Mario Augusto; Rios Osorio, Leonardo Alberto (Universidad Autónoma de Yucatán, 2024)
Background. In Colombia, people have intended to increase food production by using new alternatives in under-used areas, such as the dry Caribbean soils, where practical evaluation methods for cultivated soils are required. Objective. To evaluate the association and reliability of in situ methods to measure soil quality indicators, in comparison to laboratory analyses. Methodology.The quality of soils where the common bean is cultivated in the periods of pre-planting and post-flowering was determined in six locations at Cesar and La Guajira. Sensory analytic methods for these indicators: structure, effective rooting depth, superficial organic matter, soil cover, soil aeration, erosion control, infiltration rate and biota, were correlated to chemical microbiological variables, measured in the laboratory. Results. Deficiencies in crop structure, organic matter, soil cover, biota, and low availability of nitrogen, zinc, and boron were observed in the soil of La Guajira. Implicaciones. These results evidence the possibility to be used as low cost and high impact strategies for edaphic monitoring of common bean fields in the dry Caribbean region. Conclusion. The in situ techniques evaluated can be integrated to conventional techniques of edaphic characterization as a starting point in the identification of variables that require deterioration mitigation actions.